Assessment of sand accumulation hazard on desert highway based on variable weight-cloud model theory - Han, Feng; Wang, Chengxiang; Liu, Zelong; Liu, Zhibo (Frontiers in Earth Science, 2023)
The accumulation of sand on desert roads poses a significant threat to the smooth transportation and driving safety of these roads. To address this issue, a combined approach using the variable weight theory and cloud model theory is proposed for conducting a safety risk assessment of sand accumulation on desert roads. An evaluation index system for sand accumulation hazards is obtained through the analysis of regional geomorphological conditions, wind dynamic conditions, and engineering design factors. The evaluation index system’s constant weights are determined using the Five-Point Scale Method and Analytic Hierarchy Process. Moreover, the Variable Weight Theory is used to optimize these weights based on the actual state of the project, thereby enhancing the accuracy of risk assessment. Finally, based on the cloud model theory, a safety risk assessment model is constructed for sand accumulation hazards on desert highways. The sand accumulation hazard level of the highway is determined through this model, and the comprehensive evaluation results are visualized and presented intuitively using the MATLAB software. The experimental section of the new Wuhai-Maqin expressway sand prevention test is taken as an example for practical verification. The results show that the sand accumulation disaster level of the experimental section is grade Ⅲ, which is basically consistent with the actual engineering situation, verifying the reliability and applicability of the model. Therefore, this model could serve as an essential reference for risk assessments of sand accumulation hazards, location optimization selection, and the establishment of effective sand prevention engineering measures for desert highways.